2008
DOI: 10.1007/s00264-008-0516-0
|View full text |Cite
|
Sign up to set email alerts
|

Femoral cement within cement technique in carefully selected aseptic revision arthroplasties

Abstract: The aim of this study was to evaluate the clinical and radiological results in a group of patients who underwent aseptic revision hip arthroplasty using the cement within cement (CWC) technique. Between 1999 and 2005, 37 aseptic revision hip operations were performed. There were 30 women and five men, with an average age of 68 years. The reasons for revision were femoral stem fracture, cup failure, acetabular protrusion after hemiarthroplasty and recurrent dislocation. At an average follow-up of 46 months, non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
2
8
2
1
Order By: Relevance
“…The offset of 44 mm is attractive as most slim standard implants which are available on the market (which could be used for the same application) have smaller offsets related to the stem size, and using these stems for cement-in-cement revisions can result in higher dislocation rates. In our study the dislocation rate (we had one recurrent dislocator, 4%) was similar to other cement-in-cement studies and less than revision of total hip prosthesis in general (456, 8, 9). In addition, it is easy to change the stem position to more or less anteversion while doing revisions in recurrent dislocators.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The offset of 44 mm is attractive as most slim standard implants which are available on the market (which could be used for the same application) have smaller offsets related to the stem size, and using these stems for cement-in-cement revisions can result in higher dislocation rates. In our study the dislocation rate (we had one recurrent dislocator, 4%) was similar to other cement-in-cement studies and less than revision of total hip prosthesis in general (456, 8, 9). In addition, it is easy to change the stem position to more or less anteversion while doing revisions in recurrent dislocators.…”
Section: Discussionsupporting
confidence: 90%
“…In cases with an intact femoral cement mantle, a cement-in-cement revision is attractive (1, 4, 5, 789). However, most standard cement stems including the traditional Exeter Universal tapered stem are too long to fit in the existing cement mantle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A long cemented stem bypassing the fracture was introduced using the in-cement technique preserving the proximal cement mantle. 23 The mean functional score at final follow-up was 17.3 points (16 to 18). Four patients had pain at the lateral aspect of the thigh due to protrusion of the strut and pressure on vastus lateralis, which had disappeared after six months' follow-up in all four cases.…”
Section: Resultsmentioning
confidence: 99%
“…The Kaplan Meier survival for this group was therefore 100% (95% CI 91.4-100). The survival rate for revision for all Marcos et al reported clinical and radiological outcomes using the cement-in-cement femoral revision technique [9]. Between 1999 and 2005, 37 aseptic revision procedures were performed in 35 patients with an average age of 68 years.…”
Section: Clinical Resultsmentioning
confidence: 99%